2011
DOI: 10.1001/archgenpsychiatry.2010.180
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lifetime Comorbidity in the World Health Organization World Mental Health Surveys

Abstract: CONTEXT Although numerous studies have examined the role of latent variables in the structure of comorbidity among mental disorders, none has examined their role in the development of comorbidity. OBJECTIVE To study the role of latent variables in the development of comorbidity among 18 lifetime DSM-IV disorders in the WHO World Mental Health (WMH) surveys. SETTING/PARTICIPANTS Nationally or regionally representative community surveys in 14 countries with a total of 21,229 respondents. MAIN OUTCOME MEASU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
361
3
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 451 publications
(406 citation statements)
references
References 60 publications
33
361
3
9
Order By: Relevance
“…2 Previous studies have reported increased rates of comorbid substance abuse, anxiety, mood, personality, and disruptive behaviour disorders among adults with ADHD, persisting from childhood into adulthood. [3][4][5][6][7][8][9][10][11] Several studies have investigated the psychosocial characteristics of children in relation to accidental injuries. 12,13 Children with behavioural disorders were reported to exhibit a 1.5-times higher risk of injury compared with those without such disorders.…”
Section: Discussionmentioning
confidence: 99%
“…2 Previous studies have reported increased rates of comorbid substance abuse, anxiety, mood, personality, and disruptive behaviour disorders among adults with ADHD, persisting from childhood into adulthood. [3][4][5][6][7][8][9][10][11] Several studies have investigated the psychosocial characteristics of children in relation to accidental injuries. 12,13 Children with behavioural disorders were reported to exhibit a 1.5-times higher risk of injury compared with those without such disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Two broad factors, internalizing and externalizing, have been found to explain much of the co-occurrence among psychopathologies. (2,4,5) The internalizing dimension puts individuals at risk for depression and anxiety, and the externalizing dimension puts individuals at risk for drug abuse and conduct problems.…”
mentioning
confidence: 99%
“…12 However, some recent evidence has favored a singlefactor model. 15,18 It has also been suggested that a general internalizing factor may account for the covariation among traits related to NA and internalizing disorders. 28,29 Nonetheless, very few attempts have been made to address this particular issue empirically.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The internalizing factor is composed --at a next-order structural level --by two subfactors of distress or anxious-misery (comprising unipolar mood disorders, generalized anxiety disorder, and posttraumatic stress disorder) and fear (comprising phobic, panic, and obsessive-compulsive disorders). However, this twosubfactor higher-order internalizing structure is somewhat controversial, with recent evidence examining: 1) the role of latent internalizing and externalizing variables in the development of lifetime comorbidity 18 ; 2) the structure of common mental disorders in incarcerated offenders 15 ; and 3) the structure of common and uncommon mental disorders, 19 suggesting a less-differentiated, single-factor solution to the domain of mood and anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%